2005
DOI: 10.1016/j.molcel.2004.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Exo1 Processes Stalled Replication Forks and Counteracts Fork Reversal in Checkpoint-Defective Cells

Abstract: The replication checkpoint coordinates the cell cycle with DNA replication and recombination, preventing genome instability and cancer. The budding yeast Rad53 checkpoint kinase stabilizes stalled forks and replisome-fork complexes, thus preventing the accumulation of ss-DNA regions and reversed forks at collapsed forks. We searched for factors involved in the processing of stalled forks in HU-treated rad53 cells. Using the neutral-neutral two-dimensional electrophoresis technique (2D gel) and psoralen crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
248
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(266 citation statements)
references
References 40 publications
17
248
0
1
Order By: Relevance
“…7). These restart events may entail nucleolytic degradation rather than branch migration of the reversed forks (12), in agreement with the nucleolytic processing of reversed forks previously reported in yeast (38,39). Regardless of their source, postreplicative ssDNA gaps can certainly contribute to explain the observed accumulation of RAD51 in PARG-depleted cells.…”
Section: Discussionsupporting
confidence: 85%
“…7). These restart events may entail nucleolytic degradation rather than branch migration of the reversed forks (12), in agreement with the nucleolytic processing of reversed forks previously reported in yeast (38,39). Regardless of their source, postreplicative ssDNA gaps can certainly contribute to explain the observed accumulation of RAD51 in PARG-depleted cells.…”
Section: Discussionsupporting
confidence: 85%
“…However, based on the exo1Δ mutational spectra and genetic interaction with REV3, we previously hypothesized that EXO1 participates in at least one MMR-independent mutation avoidance pathway [12]. In agreement with our supposition, recent studies have identified a potential role for EXO1 in the maintenance and repair of stalled replication forks [20][21][22].…”
Section: Introductionsupporting
confidence: 79%
“…In addition to the role of EXO1 in PRR proposed here, EXO1 has been implicated to function in cell cycle checkpoint, fork maintenance and fork repair pathways [20][21][22]51,52]. EXO1 has been shown to play subtle roles in end-processing for mitotic recombination and function redundantly with at least one other unidentified nuclease.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Human exonuclease 1 (hExo1) is a 5Ј33Ј exonuclease (2, 3) that exists in Ia and Ib isoforms (2) and shares 27% identity with yeast Exo1 (2). Discovered in yeast (4), Exo1 participates in recombination (4,5), telomere maintenance (6, 7), mismatch repair (2,3,8), and processing of stalled replication forks (9). Consistent with its recombination function, mice devoid of Exo1 demonstrate a reduction in ssDNA formation at DSBs (7).…”
mentioning
confidence: 99%